Review article: the management of long‐term parenteral nutrition. Issue 6 (17th January 2013) - Dibb, M.; Teubner, A.; Theis, V.; Shaffer, J.; Lal, S.
Summary Background Home parenteral nutrition (HPN) is currently the management of choice for patients with chronic intestinal failure. Aim To summarise the major issues in delivering long‐term parenteral nutrition (>3 months) and assess outcome as per complications, mortality and quality of life. To assess the evidence for the therapeutic use of trophic factors such as teduglutide and to review evolving therapeutic options in the treatment of chronic intestinal failure. Methods A literature search using PubMed and MEDLINE databases was performed. Results Safe delivery of HPN relies upon individualised formulations of parenteral nutrition administered via carefully maintained central venous catheters by trained patients or carers, supported by a skilled multidisciplinary team. Early diagnosis and treatment of complications including catheter‐associated blood stream infection (reported incidence 0.14–0.83 episodes/patient‐year on HPN) and central venous thrombosis (reported incidence 0.03 episodes/patient‐year) is important to minimise mortality and morbidity. There is a significant variation in the reported incidence of both hepatobiliary complications (19–75%) and advanced liver disease (0–50%). Five‐year survival rates in large centres are reported between 60% and 78% with survival primarily related to underlying diagnosis. Long‐term survival remains higher on HPN than with intestinal transplantation. The role of intestinal lengthening procedures is yet to be validated in adults. Conclusions Home parenteral nutrition delivered by skilled nutrition teams has low incidences of catheter‐related complications. Most deaths relate to the underlying disease. Therapies such as teduglutide and small bowel transplantation appear promising, but home parenteral nutrition appears likely to remain the bedrock of management in the near term.